The behavioral changes of birds as a result of urban noise levels - Kusholany; Handayani; Setia, Tatang Mitra; Indarjani (Journal of Character and Environment, 2025)
Background: Bird conservation in Indonesia is still focused on the areas of conservation of specified government. As in the nature reserves, wildlife clan asylum and national park. Nevertheless there are birds that live outside conservation areas such as forest city. DKI Jakarta as the capital city of Indonesia with a population of the most populous and has a forest city as a habitat of birds in urban areas, it become necessary to know research, equity, diversity, wealth, abundance, similarity species of birds, the difference in noise level and noise influence toward activity-voiced bird in three forest city of DKI Jakarta. Methods: Data retrieval method using point count with 24 point edge and central region in each forest city. Findings: Based on the findings presented in Chapter IV of the thesis, the study showed that higher noise levels and greater human presence significantly reduced bird vocal activity across three urban forests in Jakarta. The average noise level was highest in PT JIEP City Forest (66.55 dB), while human activity peaked in Hutan Kota Srengseng with 152 individuals recorded. A statistically relevant pattern was found: bird vocalization activity and the number of vocalizing birds were highest in areas with lower noise and human presence, supporting the hypothesis that anthropogenic disturbance negatively impacts bird behavior. Conclusion: This study reveals that noise levels and human presence significantly affect bird vocal activity and species diversity in urban forests of Jakarta, with lower noise and fewer people correlating with higher bird sound activity and diversity, highlighting the ecological importance of preserving and managing these green spaces. Novelty/Originality of this article: This study presents a novel investigation by integrating spatial (edge vs. center zones).